THE EFFECTIVENESS OF THE EUROPEAN UNION SEAL REGIME ON THE SEAL HUNT TRADITION : IN SWEDEN AND FINLAND - Chaturiani Istiqomah Hajarwati; Melaty Anggraini (Pena Wimaya, 2025)
This study evaluates the effectiveness of the European Union Seal Regime (EUSR) in addressing seal hunting practices in Sweden and Finland, against the backdrop of growing attention to animal welfare and environmental sustainability. Using a descriptive qualitative approach, the study relies on literature review and official document analysis. The regime’s effectiveness is assessed through three dimensions: output, outcome, and impact. The findings show that in the output and outcome dimensions, the EUSR succeeded in establishing regulations and influencing member states’ behavior through strict rules and regular reporting. However, in the impact dimension, its effectiveness remains partial. Although seal populations have increased, the policy has had negative effects on local communities, particularly the Sami people, as well as on coastal fishing economies. The discussion reveals a tension between environmental conservation and the protection of local culture and economy. This study recommends a more inclusive and adaptive policy adjustment to ensure the EUSR reflects a balanced form of ecological and social justice. Keywords; European Union Seal Regime, seal hunt, regime effectiveness, animal welfare